2022
DOI: 10.1542/peds.2021-055061
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Therapy for Cerebral Palsy: A Meta-analysis

Abstract: BACKGROUND AND OBJECTIVE Bobath therapy, or neurodevelopmental therapy (NDT) is widely practiced despite evidence other interventions are more effective in cerebral palsy (CP). The objective is to determine the efficacy of NDT in children and infants with CP or high risk of CP. METHODS Cumulative Index to Nursing and Allied Health Literature, Cochrane Library, Embase, and Medline were searched through March 2021. Randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…This lack of consensus or clear definition, together with the divergence in practice and teaching, has made interpreting and generalizing any reported findings difficult. This has been compounded by shortcomings in research methodology leading to unfavourable reviews in the literature, including a call to de‐implement the approach 9,10 …”
Section: Historical Contextmentioning
confidence: 99%
“…This lack of consensus or clear definition, together with the divergence in practice and teaching, has made interpreting and generalizing any reported findings difficult. This has been compounded by shortcomings in research methodology leading to unfavourable reviews in the literature, including a call to de‐implement the approach 9,10 …”
Section: Historical Contextmentioning
confidence: 99%
“…However, the results of the studies on the effects of NDT on motor development are contradictory (Damiano, 2013; Te Velde et al., 2022). Although minimal changes occur with NDT in infancy, recent systematic reviews on the effect of early intervention in high‐risk infants have shown that NDT does not improve neurodevelopmental outcomes (Blauw‐Hospers & Hadders‐Algra, 2005; Blauw‐Hospers et al., 2007: Spittle et al., 2012; Te Velde et al., 2022). Also, passive techniques like stretching and passive range of motion exercises are generally provided with “hands‐on” techniques.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of the studies on the effects of NDT on motor development are contradictory (Damiano, 2013;Te Velde et al, 2022). Although minimal changes occur with NDT in infancy, recent systematic reviews on the effect of early intervention in high-risk infants have shown that NDT does not improve neurodevelopmental outcomes (Blauw-Hospers & Hadders-Algra, 2005;Blauw-Hospers et al, 2007: Spittle et al, 2012Te Velde et al, 2022). Also, passive techniques like stretching and passive range of motion exercises are generally provided with "hands-on" techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Despite universal beliefs about the benefits of early intervention, systematic reviews6 7 indicate that traditional early intervention is ineffective for infants with CP, with most trials failing to confer any motor gains 6. Significant shortcomings exist within standard early intervention for infants with CP and research studies to date in that: (1) intervention is late, not early due to delayed diagnosis8; (2) many traditional therapy approaches involve hands-on therapist-executed movements, where the infant’s role in movement generation is passive not active, all of which have been proven ineffective and fail to harness neural plasticity7 9; (3) intervention is underdosed10; and (4) major methodological flaws exist in previous trials. In addition, early identification of risk for CP was historically less accurate leading to inadvertently recruiting and treating normal infants within CP trials, reducing statistical power 6…”
Section: Introductionmentioning
confidence: 99%
“…When usual care eventually starts it is often not evidence-based, as it typically involves traditional passive movement approaches, which have been proven ineffective 7 9. Neuroscience preclinical data strongly support early active movement training as an intervention for improving brain reorganisation and outcomes after early brain damage.…”
Section: Introductionmentioning
confidence: 99%